Application of SMED to reduce setup in the ward of an obstetric hospital - Freitas, Alina de Oliveira; Pimentel, Cristiane Agra; Maia, Vanessa Kelly Freitas; Araujo, Andressa Clara Barbosa de (Brazilian Journal of Production Engineering, 2025)
This study investigates the application of Single Minute Exchange of Die (SMED) to reduce setup time in an obstetric hospital ward in Feira de Santana, Bahia. The objective was to optimize bed release, minimizing delays in care and improving operational efficiency. The research followed four stages: data collection, chronoanalysis of activities, review of Standard Operating Procedures (SOPs), and application of training. Direct observation identified bottlenecks in the discharge and bed cleaning process. The chronoanalysis revealed long waiting times between medical release and the start of cleaning, in addition to the lack of standardization of activities. As a solution, SOPs were reviewed, training was applied, and communication tools, such as radios and the Kamishibai system, were implemented. The results showed a 20% reduction in bed cleaning time and a 50% decrease in the waiting time to start cleaning. The estimated annual savings were R 15,000.00. The study concludes that standardizing processes and training teams are essential for the sustainability of improvements. Future research can explore the integration of SMED with Artificial Intelligence and other hospital management tools.